'Juntos Somos Fuertes': Writing Participatory Corridos of Solidarity through a Critical Translingual Approach. (9th September 2021) - De Los Ríos, Cati V; Seltzer, Kate; Molina, Arturo
Abstract: Changing demography in the Southwest USA has shifted the racial compositions of many neighborhoods that were once predominantly African American to majority Latinx immigrant communities (Orfield and Frankenberg 2014 ). Today, it's common for these two youth communities to learn side-by-side in urban and suburban classrooms where they are often positioned to share each other's cultural practices (Martinez 2017 ). However, language and literacy research often positions these two minoritized communities as mutually exclusive (Paris 2010 ). Moreover, while researchers have urged the analysis of these two youth communities comparatively few studies document classroom units that cultivate spaces for 'linguistic solidarity' (Martinez 2017 ). Drawing from an ethnographic study of an 11th-grade ethnic studies class, the authors explore how Arturo (third author) took up a critical translingual approach in his classroom where students—both Latinx and African American—collaborated through the cowriting of corridos (Mexican ballads) about their lived experiences with in/justice. The findings demonstrate the ways that this unit invited students to write across racial, ethnic, and linguistic borders and fostered language and cultural sharing, political consciousness, and solidarity.